Chromosomal aberrations in peripheral blood lymphocytes of prostate cancer patients treated with IMRT and carbon ions - Hartel, Carola Sabine; Nikoghosyan, Anna; Durante, Marco; Sommer, Sylwester; Nasonova, Elena; Fournier, Claudia; Lee, Ryonfa; Debus, Jürgen; Schulz-Ertner, Daniela; Ritter, Sylvia (Radiotherapy and oncology, 2010)
Background and purpose - To investigate the cytogenetic damage in blood lymphocytes of patients treated for prostate cancer with different radiation qualities and target volumes. - Materials and methods - Twenty patients receiving carbon-ion boost irradiation followed by IMRT or IMRT alone for the treatment of prostate cancer entered the study. Cytogenetic damage induced in peripheral blood lymphocytes of these patients was investigated at different times during the radiotherapy course using Giemsa staining and mFISH. A blood sample from each patient was taken before initiation of radiation therapy and irradiated in vitro to test for individual radiosensitivity. In addition, in vitro dose-effect curves for the induction of chromosomal exchanges by X-rays and carbon ions of different energies were measured. - Results - The yield of chromosome aberrations increased during the therapy course, and the frequency was lower in patients irradiated with carbon ions as compared to patients treated with IMRT with similar target volumes. A higher frequency of aberrations was measured by increasing the target volume. In vitro, high-LET carbon ions were more effective than X-rays in inducing aberrations and yielded a higher fraction of complex exchanges. The yield of complex aberrations observed in vivo was very low. - Conclusion - The investigation showed no higher aberration yield induced by treatment with a carbon-ion boost. In contrast, the reduced integral dose to the normal tissue is reflected in a lower chromosomal aberration yield when a carbon-ion boost is used instead of IMRT alone. No cytogenetic “signature” of exposure to densely ionizing carbon ions could be detected in vivo.
Gesehen am 24.03.2023